2019
DOI: 10.1080/19396368.2019.1680764
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for sperm retrieval from males with azoospermia who are eligible for testicular sperm extraction (TESE)

Abstract: The aim of this study was to evaluate the predictive value of factors in infertile male patients to retrieve sperm from their testicles before they undergo testicular sperm extraction (TESE). In total, 64 males were enrolled in this study. Infertility was identified as obstructive azoospermia (OA); non-obstructive azoospermia (NOA); Klinefelter syndrome (KS); and cryptozoospermia (Crypt). Age, body mass index and concomitant conditions were noted. Testicular volumes, serum levels of Follicle-Stimulating Hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
0
23
1
1
Order By: Relevance
“…Complications such as hematoma, testicular brosis and testicular atrophy were less frequent in microTESE groups compared with cTESE groups 11 . The rates of hematoma and dehiscence were signi cantly different between the TESE-positive group and the TESE-negative group 2 . In the current study, the complication rate showed no signi cant difference between the cTESE and microTESE groups and there was also no signi cant difference in the subgroup histopathology analysis.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Complications such as hematoma, testicular brosis and testicular atrophy were less frequent in microTESE groups compared with cTESE groups 11 . The rates of hematoma and dehiscence were signi cantly different between the TESE-positive group and the TESE-negative group 2 . In the current study, the complication rate showed no signi cant difference between the cTESE and microTESE groups and there was also no signi cant difference in the subgroup histopathology analysis.…”
Section: Discussionmentioning
confidence: 83%
“…Yalcin Kizilkan et al found that a previous successful testicular biopsy and higher testicular volume were predictive parameters for microTESE patients 6 . One study reported no predictors of successful outcomes, whereas tobacco usage was a predictor factor for patients with a negative TESE 2 . Another recent study concluded that there were no de nite predictors for sperm retrieval, except for chromosome disease; however, Sertoli cell-only histopathology was associated with a reduced chance of harvesting spermatozoa 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, sperm retrieval using conventional TESE has only proved to be successful in a subset of patients, approximately 50%, regardless of the cause of azoospermia (obstructive or nonobstructive). 39 , 82 , 83 , 84 Spermatogenesis is not equally distributed throughout the testis, and it would appear that sperm quality is better in areas with high tissue perfusion. 85 The high accuracy of CEUS in assessing blood perfusion and microvascular architecture of the testes may suggest that this technique could help increase the probability of sperm retrieval.…”
Section: Ceus Beyond Testicular Lesionsmentioning
confidence: 99%